Sistem Informasi Pengolahan Nilai Siswa Berbasis Web Pada SMP Muhammadiyah Imogiri Yogyakarta - Supriyanta Supriyanta; Elsa Murbiastuti (Universitas Bina Sarana Informatika, 2018)
ABSTRACT - Utilization of information technology is needed by schools to improve education management productivity. Utilization of information technology can provide benefits on time and energy efficiency. Saving time and speed of presentation of information due to the application of information technology will provide an opportunity for teachers and school administrators to improve the quality of service to students. SMP Muhammadiyah Imogiri Yogyakarta is a system to support and facilitate the processing of student value. The goal is to create a web-based information system that is implemented for the processing of value and overcome the difficulty of delivering daily re-information, assignments, semester midterms, semester final repetition. Based on observational research, literature study, and interviews that have been done, then designed a student information processing system using waterfall method into a solution to solve existing problems. Student value information processing system makes it easier for teachers, homeroom teachers, as well as teaching sections in processing student value and supporting the process of teaching and learning. Keywords: Information, System, Student Value Processing